Consanguinity and congenital heart disease in offspring - Aris Fazeriandy; Muhammad Ali; Johannes H. Saing; Tina Christina L. Tobing; Rizky Adriansyah (Indonesian Pediatric Society, 2018)
Background Congenital heart disease (CHD) is a common congenital abnormality in children. Consanguineous marriage has been identified as a risk factor of CHD. There was an autosomal recessive pattern of inheritance seen in children with some forms of congenital heart disease. Objective To assess the possible association between consanguineous marriage and congenital heart disease incidence in the offspring. Methods A case-control study was conducted from March to May 2016 on pediatric patients at H. Adam Malik General Hospital, Medan. Subjects were allocated into two groups, 100 children with CHD in the case group, and the rest in the control group. Data were analyzed using Chi-square and logistic regression tests. In the present study, P value less than 0.05 was considered statistically significant. Results In the case group, 14 patients (14%) were born of consanguineous marriages. In the control group, only 5 patients (5%) were born of consanguineous marriages. There was a significant association between consanguineous marriage and CHD (OR 1.551; 95%CI 1.138 to 2.113). Based on the result of multivariate analysis, consanguineous marriage was a risk factor for CHD in offspring (Wald=4.525; P=0.033). Conclusion Consanguineous marriage is a risk factor for CHD in offspring.